Early Pleistocene charophyte flora from Dursunlu (Ilgın Basin, Turkey): palaeoecological implications - TUNOĞLU, CEMAL; Sanjuan, Josep; Demirci, Elvan (Review of Palaeobotany and Palynology, 2023)
© 2023 Elsevier B.V.Here, a charophyte assemblage from lower Pleistocene deposits at the coal mine locality of Dursunlu (Ilgın Basin, Turkey) is described and illustrated for the first time. The assemblage is composed of 11 species recovered from 50 samples taken from an 18 m-thick sedimentary sequence. The base of the sequence is dominated by lignites and organic-rich claystones/siltstones with root marks attributed to palustrine facies. The charophyte assemblage in this palustrine interval is dominated by Chara vulgaris and C. globularis. The upper part of the section is constituted by light grey-yellowish marls, siltstones and a limestone bed related to shallow lacustrine deposits. Two charophyte species dominate this lacustrine interval, Chara hispida and Nitellopsis obtusa, which occurred in intervals in association with Chara pappii, Chara molassica var. notata, Chara sp.1, Chara sp.2, Sphaerochara prolifera, Sphaerochara intricata and Lychnothamnus barbatus var. antiquus. The palaeoenvironmental characteristics and evolution of the Ilgın palaeolake during the Early Pleistocene (Günz glaciation) are inferred from a facies analysis and the ecological requirements of the charophyte assemblages. The results suggest that during this glacial period, the Ilgın Basin was occupied by a very shallow eutrophic lake with a dense palustrine vegetation belt, which evolved to a shallow (2–15 m deep), stable, oligotrophic, alkaline and oligohaline lake. The increase in water availability in the palaeolake can be related to climatic oscillation during the Günz glaciation. Finally, the lake depocentre migrated towards the NW due to tectonism, and these deposits were later subjected to intense pedogenic alteration.